1996
DOI: 10.1007/s004410050676
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of growth hormone receptors/binding proteins in immune tissues

Abstract: It is well established that the activity and proliferation of lymphoid cells and lymphoid organs are stimulated by growth hormone. These actions on lymphoid cells may be direct or mediated by actions on the epithelial and non-immune tissue cells that regulate immune function. The occurrence and cellular localization of growth hormone receptors in immune tissues has therefore been investigated to determine the target-sites of growth hormone action. Growth hormone receptor mRNA was first detected by Northern blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 54 publications
(69 reference statements)
1
16
0
2
Order By: Relevance
“…This group [58] subsequently reported that cells expressing GHR also expressed receptors for PRL. Similarly, GHR mRNA was found to be widely distributed in the lymphoid tissues of fowl [59]. Chen, et al, [60] examined cells from bovine fetal spleen and thymus tissue and found GHR expression in early to mid-gestational age with expression diminishing in later gestation.…”
Section: Distribution Of Gh and Prl Receptorsmentioning
confidence: 98%
“…This group [58] subsequently reported that cells expressing GHR also expressed receptors for PRL. Similarly, GHR mRNA was found to be widely distributed in the lymphoid tissues of fowl [59]. Chen, et al, [60] examined cells from bovine fetal spleen and thymus tissue and found GHR expression in early to mid-gestational age with expression diminishing in later gestation.…”
Section: Distribution Of Gh and Prl Receptorsmentioning
confidence: 98%
“…GH receptor (GHR) immunoreactivity was detected using a polyclonal antibody (at a concentration of 1:400) raised in rabbits against recombinant chicken GH binding protein (rcGHBP) (Huang et al 1993, Hull et al 1996, using the ABC technique, as detailed above. The specificity of staining was demonstrated by replacement of the primary antibody with non-immune rabbit serum (NRS) or PBS.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The possibility that SLD serum and liver may be deficient in immunoreactive GHBP/GHR or contain GHBPs or GHRs of anomalous size was evaluated by Western blot analysis, as previously described (Hull et al 1996a). GHR/ GHBP-like proteins in hepatic homogenates and serum aliquots were detected by a rabbit polyclonal antiserum ( cGHBP at a final dilution of 1:2000) (Hull et al 1996a).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…GHR/ GHBP-like proteins in hepatic homogenates and serum aliquots were detected by a rabbit polyclonal antiserum ( cGHBP at a final dilution of 1:2000) (Hull et al 1996a). For comparative purposes, another polyclonal antibody ( CH17) raised in mice against a putative membranebound chicken GHBP (Dr W Baumbach, American Cyanmid, Princeton, NJ, USA) was also used.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation